Kinerja Jembatan Rangka Baja yang Diperkuat dengan GFRP (Glass Fiber-Reinforced Polymer) - Suyadi .; Eddy Purwanto; Ferry Taurus (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Analysis of the data in this study is focused on a comparison of the results of direct testingdeflection field with SAP 2000 analysis and manual calculation of loading field and standard(RSNI T-02-2005) with a maximum deflection limit bridge.Based on the results obtained by calculation of loading field: percentage reduction of deflectiontest results without the GFRP reinforcement compared to after given the GFRP reinforcement ondirect testing field, SAP 2000 analysis, and manual calculation respectively, they are obtained4.934 %, 0.7097%, and -0,6804 %. Based on the results of the calculation deflection of theloading standard: percentage reduction of deflection test results without the GFRP reinforcementcompared to after given the GFRP reinforcement on SAP 2000 analysis and manual calculationrespectively, they are obtained 2,0212 % and -0.17557 %. The Values of deflection are calculatedstill below 18.75 cm as deflection limit L/240.